1984
DOI: 10.1002/art.1780271101
|View full text |Cite
|
Sign up to set email alerts
|

Anticollagen antibodies and immune response gene products in rheumatoid arthritis

Abstract: Circulating antibodies to native and denatured types I and I1 human and bovine collagens were assayed in patients with rheumatoid arthritis (RA), patients with other rheumatic diseases, and normal individuals. A subgroup of this population was also assayed for reactivity with typing reagents which detect determinants (MT and HLA-DR) present in human immune response gene products. The mean titers of antibodies to each collagen tested were not significantly higher in RA patients when compared with patients who h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Since Steffen and Timpl (1) showed, in 1963, that the antibodies to homogenates of joint capsule cartilage from RA patients were reactive with collagen, many studies have confirmed that sera from patients with RA have antibodies to a variety of collagens (1)(2)(3)(4)(5)(6)(7)(8)(9). When tested, these antibodies have been found at higher titer in patients' synovial fluid as well (9-1 1).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since Steffen and Timpl (1) showed, in 1963, that the antibodies to homogenates of joint capsule cartilage from RA patients were reactive with collagen, many studies have confirmed that sera from patients with RA have antibodies to a variety of collagens (1)(2)(3)(4)(5)(6)(7)(8)(9). When tested, these antibodies have been found at higher titer in patients' synovial fluid as well (9-1 1).…”
Section: Discussionmentioning
confidence: 99%
“…These antibodies have been demonstrated to react to some degree with all types of collagen tested (9), but major interest has centered on type I collagen, which is found predominantly in skin, bone, vessels, and at joint surfaces, and type I1 collagen, which is found in hyaline cartilage. Antibodies have been shown to react with native collagens (M), denatured collagens (2), or both native and denatured collagens (3,8,9,11).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations